Efektivitas E-Book KIA Terhadap Pengetahuan Kesehatan Ibu dan Anak pada Ibu Hamil - Daini Zulmi; Atin Suhartini; Sekar Dinda Dayana; Muffarohah muffarohah; Annisa'ul Awaliyah; Cica Refita (Akademi Kebidanan La Tansa Mashiro, 2021)
This E-Book on Maternal and Child Health (MCH) contains information on the Maternal and Child Health book which was created to provide information on Maternal and Child Health digitally in a link format equipped with voice recordings. (Depkes RI, 2015). The purpose of this study was to determine the effectiveness of developing an E-Book on Maternal Child Health with knowledge of Maternal and Child Health in pregnant women at the Kalanganyar Health Center in 2021. The type of research used was case control, the population was pregnant women who were in the work area of the Kalanganyar Health Center, the number of samples was 48. person. The results of the study can be seen that pregnant women who understand the contents of Maternal and Child Health who use E-Books are more effective than printed books because the number who understands E-Books on Maternal Child Health (51.2%) while those who understand MCH handbooks (48.7 %). A small percentage (16.6%) of pregnant women in the community health center did not understand the MCH E-Book and who did not understand the MCH printed book (20.8%). Mother's understanding is higher with e-books than printed books, because at this time most pregnant women interact with gadgets so that mothers prefer to listen rather than read. In order to make it easier for health workers or pregnant women regarding maternal and child health information, it must be supported by technology that is connected to a system that has a good network.Based on the results of the chi square test, the P-Value value is 0.002 where p≤0.05, then the e-book can be effective in increasing the knowledge of pregnant women. The value of Odds Ratio (OR) = (1.894-142.501) which means that the use of printed MCH books is 16 times risky, pregnant women do not understand the contents of MCH books. Mother's understanding is higher with e-books than printed books, because at this time most pregnant women interact with gadgets so that mothers prefer to listen rather than read. In order to make it easier for health workers or pregnant women regarding maternal and child health information, it must be supported by technology that is connected to a system that has a good network.